Improving the Sensitivity of Surface-Enhanced Laser-Induced Breakdown Spectroscopy by Repeating Sample Preparation - Yang, Xinyan; Li, Xiangyou; Cui, Zhifeng; Yao, Guanxin; Zhou, Zhengxian; Li, Kuanguo (Frontiers in Physics, 2020)
To improve the detection sensitivity of aqueous solution using surface-enhanced laser-induced breakdown spectroscopy (SENLIBS), the number of sample preparation in a fixed point was increased. The trace elements (Cu, Pb, Cd, and Cr) in an aqueous solution were detected successfully using this method. The results showed that the spectral intensity was strengthened. The limit of detection (LoD) values were reduced from 0.034 0.058 to 0.019 0.033 μg/mL by increasing number of repeating sample preparation. This demonstrated that quantitative analysis sensitivity of SENLIBS could be improved by increasing the sample preparation repeatability.